Psychiatric nursing research based on nursing for the whole person theory - M. Poggenpoel (AOSIS, 1996)
One of the determinants for decision-making in conducting psychiatric nursing research is the researchers' framework of reference he/she works from. This framework of reference refers to the way in which researcher views reality and is called a paradigm and consists of metatheoretical, theoretical and methodological assumptions. The metatheoretical assumptions reflect the researcher's view of a person, health, nursing and environment. These are beliefs and cannot be tested and are accepted to be true for the researcher. The theoretical assumptions are deducted from the metatheoretical assumptions and can be formulated into central statements or hypothesis and be validated through research. Nursing for the Whole Person Theory has a set of metatheoretical, theoretical and methodological assumptions that can provide direction in conducting psychiatric nursing research. In this paper the application of Nursing for the Whole Person Theory in conducting psychiatric nursing research will be demonstrated by using a completed psychiatric nursing research study as an example.